HelixComplex snail mucus exhibits pro-survival, proliferative and pro-migration effects on mammalian fibroblasts. Issue 1 (December 2018) - Trapella, Claudio; Rizzo, Roberta; Gallo, Stefania; Alogna, Andrea; Bortolotti, Daria; Casciano, Fabio; Zauli, Giorgio; Secchiero, Paola; Voltan, Rebecca
Abstract Snail mucus is a mixture of active substances commonly thought to have healthy properties for the treatment of skin disorders. Although snail mucus is an ingredient of several cosmetic and para-pharmaceutic products, a comprehensive characterization of chemical composition and biological effects is still missing. Crude purified extracts fromHelix aspersa muller mucus (HelixComplex) were prepared and, after chemical characterization, tested onin vitro experimental models. Differently from what expected, HelixComplex was characterized by the presence of small amounts of glycolic acid and allantoin. By using differentin vitro assays on fibroblast cultures, we found that HelixComplex lacked of cytotoxicity, protected cells from apoptosis (p < 0.05) and, importantly, was able to significantly induce cell proliferation and migration through direct and indirect mechanisms. These effects were associated to morphological changes, cytoskeleton re-organization and release of cytokines. In conclusion, our findings suggest that snail mucus biological effects are attributable to cell proliferation and migration, and pave the way for further investigating snail mucus potential as therapeutic agent.